SOSIALISASI AKUNTANSI DASAR UNTUK UMKM DI KECAMATAN CIPAYUNG JAKARTA TIMUR - Lidya Primta Surbakti; Dewi Darmastuti; Ekawati Jati Wibawaningsih (Bajang Institute, 2025)
MSMEs often face financial problems such as poor cash flow, inaccurate recording,. These problems are also experienced by MSMEs in Cipatung District, East Jakarta. Therefore, this Community Service (PkM) activity aims to improve MSMEs' understanding of basic knowledge about accounting that can help them manage their finances better, ensure proper documentation, which ultimately support the stability and growth of their businesses. The method used is to conduct socialization of basic accounting in accordance with the latest standards carried out by Lecturers of the Accounting Department, assisted by the Master of Accounting students, FEB UPN